Mortality trends for tuberculosis and sarcoidosis in English populations, 1979-2008. - Duncan, M; Goldacre, M (2012)
SETTING: Analysis of data sets that included both underlying and all contributing causes of death (together termed 'mentions'): the Oxford Record Linkage Study, 1979-2008, and England national data, 1995-2008. OBJECTIVE: To determine mortality trends for the granulomatous lung conditions tuberculosis (TB) and sarcoidosis in the Oxford region (1979-2008) and England (1995-2008). RESULTS: Mortality for mentions of TB in the Oxford region declined from 39.7 deaths per million population in 1979 to 9.0 in 2008. The corresponding rates for underlying cause were 17.1, falling to 4.5. In England, mortality rates from TB fell from 18.5/million in 1995 to 12.2 in 2008 (mentions), and from 9.3 in 1995 to 6.5 in 2008 (underlying cause). Numbers of deaths from sarcoidosis in Oxford were very small, and showed no significant trend. For the much larger England population, mortality rates based on mentions were 3.6/million in 1995 and 4.2 in 2008; the corresponding rates for sarcoidosis as underlying cause were 2.1 and 2.3. CONCLUSION: TB mortality is still declining in England, despite a recent resurgence in the prevalence of the disease. Mortality from sarcoidosis has been largely stable. The conventional statistic of underlying cause of death missed almost half of all certified TB and sarcoidosis deaths.